Design and fabrication of multifunction laptop cooler / Nadzirul Azizi Norizam - Norizam, Nadzirul Azizi (2023)
Introduction to device that call laptop cooler or cooling pad. A laptop/notebook cooler, cooling pad, cooler pad or chill mat is an accessory for laptop computers that helps reduce their operating temperature, which is normally used when the laptop is unable to sufficiently cool itself. The project is chosen because of the problem that people keep facing daily. A major problem is in the feature of the design of the laptop pad. The objective of this work is about to determine the possibility to add feature that have been design for the laptop pad. The current design of this study is proposed for cooling the laptop temperature. The project focus to add some feature to help multiple a use for the laptop pad. It was found that many companies and engineer innovate a table of multifunction. The proposed of multifunction of the laptop pad is to ease the user to develop their life. The method that used for this project was milling, cutting, and drilling.